2020
DOI: 10.1177/0896860819880101
|View full text |Cite
|
Sign up to set email alerts
|

“Can I go to Glasgow?” Learnings from patient involvement at the 17th Congress of the International Society for Peritoneal Dialysis (ISPD)

Abstract: Background: Recognition of the discrepancy between the research priorities of patients and health professionals has prompted efforts to involve patients as active contributors in research activities, including scientific conferences. However, there is limited evidence about the experience, challenges, and impacts of patient involvement to inform best practice. This study aims to describe patient and health professional perspectives on patient involvement at the Congress of the International Society for Periton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A second study reported using a partially validated tool, 77 and specifically focused on how the conference impacted self-assessment of comfort with providing end of life care. For the remaining studies, 13 (18% of those using surveys/interviews) described using an evaluation framework to inform their study, including tool development, 3 , 22 , 29 , 38 , 41 , 49 , 55 , 64 , 68 , 69 , 74 , 83 of which 3 22 , 64 , 69 referenced the same primary source 70 – a scoping review whose goal was to develop a conference evaluation framework. Of the remaining 24 (32% of those using surveys/interviews), only two studies reported performing any pilot testing of their tool, 42 , 54 with an additional three 29 , 72 , 80 suggesting the work itself represented a pilot study for tool assessment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A second study reported using a partially validated tool, 77 and specifically focused on how the conference impacted self-assessment of comfort with providing end of life care. For the remaining studies, 13 (18% of those using surveys/interviews) described using an evaluation framework to inform their study, including tool development, 3 , 22 , 29 , 38 , 41 , 49 , 55 , 64 , 68 , 69 , 74 , 83 of which 3 22 , 64 , 69 referenced the same primary source 70 – a scoping review whose goal was to develop a conference evaluation framework. Of the remaining 24 (32% of those using surveys/interviews), only two studies reported performing any pilot testing of their tool, 42 , 54 with an additional three 29 , 72 , 80 suggesting the work itself represented a pilot study for tool assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Patients and caregivers are another group for whom inclusion has been a growing priority and seven studies within this review specifically included these individuals as stakeholders, potentially reflecting the growing importance their inclusion in conference planning and implementation has on preventing discrepancies between patient and health professional priorities. 38 , 41 , 63 , 69 Patient and caregiver conference participation avenues varied, ranging from being the primary audience for improved education and involvement in medical and scientific discussions, 63 , 101 to inclusion as planners and speakers to better incorporate their feedback into research, health care, and policy. 38 , 41 This trend reflects a similar shift in broader health care and research toward patient inclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can enhance scientific learning, clarify the relevance of research to patient care, broaden the research agenda and knowledge exchange, inspire new and different perspectives, democratize access to research and increase the potential of impact of research—beyond the walls of the conference . Patients who have attended scientific meetings report that they gain knowledge and ownership of their own health, and clinicians note that they feel more motivated to change and innovate how they practice . Conferences can also provide an opportunity to establish patient‐researcher partnerships.…”
mentioning
confidence: 99%